Effect of Work Motivation and Discipline on Employee Performance of PT. Pos Indonesia Lubuk Pakam - Khaula Anjelina Mendropa (Junal Ilmu Manajemen, 2018)
Motivation and discipline are directly related to employee performance. Motivation and discipline that are felt directly by employees can reduce performance or improve employee performance. Employees who feel motivated and disciplined about the work obtained will have an impact on improving the performance of an agency as a whole. This study aims to determine the effect of work motivation and work discipline on the performance of 30 Pos PT Lubuk Pakam employees. The analytical method used is multiple linear regression analysis, simultaneous test (F-Test), partial test (t-test). The results of the analysis that motivation and work discipline simultaneously have a significant positive effect on employee performance at PT Pos Indonesia Lubuk Pakam. Partially motivation and work discipline have a significant positive effect on the performance of employees of PT. Pos Indonesia Lubuk Pakam.